2014
DOI: 10.1128/jb.02310-14
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Regulation of thedevOperon by MrpC2 and FruA during Myxococcus xanthus Development

Abstract: Proper expression of the dev operon is important for normal development of Myxococcus xanthus. When starved, these bacteria coordinate their gliding movements to build mounds that become fruiting bodies as some cells differentiate into spores. Mutations in the devTRS genes impair sporulation. Expression of the operon occurs within nascent fruiting bodies and depends in part on C signaling. Here, we report that expression of the dev operon, like that of several other C-signal-dependent genes, is subject to comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 60 publications
11
57
0
Order By: Relevance
“…MrpC and FruA are transcription factors that cooperatively bind to the dev promoter region and appear to activate transcription (9). Also, MrpC appears to activate transcription of fruA (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MrpC and FruA are transcription factors that cooperatively bind to the dev promoter region and appear to activate transcription (9). Also, MrpC appears to activate transcription of fruA (15).…”
Section: Discussionmentioning
confidence: 99%
“…1). Since the dev operon is a direct target of transcriptional activation by MrpC and FruA (9), a simple model proposes that dev expression governs commitment to sporulation (5). However, recent work showed that deletion of the dev promoter or the first gene of the operon, devI, suppresses the sporulation defects of devR and devS mutants (10).…”
mentioning
confidence: 99%
“…Combinatorial regulation by MrpC2 and FruA has been documented for four other developmental genes or operons of M. xanthus (19)(20)(21)(22) in addition to the dev operon (18). All of these genes and operons depend on C-signaling for expression during development (23)(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…LadA binds to DNA about 350 bp downstream of the dev promoter (P dev ) and positively regulates transcription (17). MrpC2 appears to bind cooperatively with FruA to two sites upstream of P dev (18). Binding of the two transcription factors to a site located immediately upstream of P dev is necessary for expression.…”
mentioning
confidence: 99%
“…Thus far, about 100 basic structures and 500 structural analogs have been discovered in myxobacteria and have been fully characterized chemically, which account for about 3.5% of the presently known secondary metabolites of microbial origin [5][6]. The diversity of the chemical structures and action mechanisms of the metabolites from myxobacteria can even be compared with those from Streptomyces [7][8]. Therefore, myxobacteira are not only important in fundamental studies, but also alluring by industrial application.…”
Section: Introductionmentioning
confidence: 99%